A toss up? Comparing tax revenues from the amount a and digital service tax regimes for developing countries - Vladimir Starkov; Alexis Jin (South Centre, 2024)
In this paper, we attempt to estimate the tax revenues to be gained by the Member States of ATAF, WATAF, AU and the South Centre under the Amount A and an alternative stylized DST taxation regime. Our research demonstrates that the comparative revenue effects of the Amount A and DST taxation regimes largely depend on (a) the mix of relevant domestic economic activities at market jurisdictions (i.e., revenues sourced to the country as a market jurisdiction under Amount A and the level of revenues from automated digital services generated in the country), (b) design details of the DST regime such as the DST tax rate and the nature of activities to be taxed and (c) the relief from double taxation, if any, countries will grant to domestic and foreign taxpayers under DST. This paper contains analysis relying on sources of information available to private sector researchers and it does not involve review of any information that individual taxpayers provided to tax authorities.
Keywords: 300; African Tax Administration Forum (ATAF); African Union (AU); Amount A; Automated Digital Services (ADS); China; Consumption Expenditure Data; Corporate Income Tax (CIT); Digital Service Taxes (DSTs); Double Taxation; Global Tax; Global Taxation; India; International Tax; International Tax Cooperation; International Tax Reform; International Taxation; Multinational Enterprises (MNEs); Organisation for Economic Co-operation and Development (OECD); Tax; Tax Cooperation; Tax Law; Tax Policy; Tax Revenue Mobilization; Taxation; United Nations (UN); West African Tax Administration Forum (WATAF)